Processi di self-digital identity building dei protagonisti della politica locale: narrazioni social nel caso dei candidati sindaco a Napoli - Punziano, Gabriella; Padricelli, Giuseppe Michele (SocietàMutamentoPolitica, 2023)
Starting from the assumption related to the personalization of politics (Castells, 2008; Barile, 2014) that open to those disintermediated ways in which build relations with the electors, this paper is focused on those identity building processes digitally held. The digital-self that politicians self-build on digital media and on the social media-sphere thanks to specific narrative frames. The case study adopted delas with the local election in Naples in October 2021. It retraces the narrations self-built by the candidates on Facebook and Twitter. The empirical work is projected to a digital-mixed content analysis (Punziano, 2022) oriented to define profiles and trajectories of the self-identity building process of candidates, the features of those identities, the configuration of the relations with the connected electors and the impacts of their communication strategies on the electoral results. In line with these objectives, we intend to comprehend if the digital self-constructions of candidates have been pushed by the same electoral event, how they were different before the candidates’ nominations and if they shut down later the electoral campaign.